PENGGUNAAN MODEL PEMBELAJARAN LEARNING CYCLEY UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ALAT GERAK - Suhendar, Suhendar; Jayadinata, Asep Kurnia; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2019)
The research aims to improve students learning outcomes through the use of learning cycle models in the science learning of motion tool content. This research was conducted in class V of SDN Bojongloa District Kasomalang Subang. This research is based on Brunner learning theory and the paradigm of constructivism The research method used is a classroom action research method with three cycles. The subject of this research totaled are 33 students. Data collection techniques or procedures used are interviews, observations, field records, and test learning outcomes. The results showed that by implementing learning cycle models can improve student learning outcomes on the content of motion tools. This is showed by the result of cycle I is 60.6% of students complete. Cycle II is 84.8% of students complete. Then cycle III is 93.9% of students complete to the minimun criterion 70.